Modelling of Gust Factor Based Dynamic Loading of Buildings Using Python Programming - Pankaj Dumka; Rishika Chauhan; Amit Srivastava (Computational Engineering and Physical Modeling)
In this research article, Python programming has been used to model the dynamic wind loading on the structures by using the Gust factor approach. The evaluation has included the design wind velocity and pressure, the Gust factor, and wind loads, which are in sync with the stability criteria as outlined in the IS 875 (Part 3), 2015. One practical numerical problem has been addressed to assess the accuracy and reliability of the developed functions, by providing a detailed step-by-step explanation of the programming process and algorithm. The results thus obtained have demonstrated a very good agreement with the results which have been obtained by using the analytical approach. The observations have indicated that the windward loads exhibit higher magnitudes than those in the across-wind direction. Notably, it has also been observed that the wind loads decrease with the height due to reductions in the tributary area and the top mean floor height.